Managing mother’s own milk for very preterm infants in neonatal units in 11 European countries - Rodrigues, C (2021)
Feeding with human milk has been recognised as an essential component of newborn care and is especially important for infants born very preterm (VPT, below 32 weeks of gestation) who face higher risks of adverse outcomes. WHO recommends that infants who cannot be fed mother's own milk (MOM) should receive donor human milk. Direct feeding at the breast takes time to establish after VPT birth and procedures are required for expressing, collecting, storing and administering breast milk that respect microbiological safety rules and ensure nutritional and immunological quality. However, as recommendations are scarce, these procedures appear to be dependent on organizational structures and policies of the units (1-3).